2019
DOI: 10.3389/fpls.2019.01360
|View full text |Cite
|
Sign up to set email alerts
|

All for One: The Role of Colony Morphology in Bryophyte Desiccation Tolerance

Abstract: In the last decade, several works showed that even bryophytes from aquatic environments, if slowly dehydrated, can cope with desiccation in a response like the one from desert bryophytes. This led to the hypothesis that, if bryophytes from contrasting habitats can have similar responses, desiccation tolerance (DT) is partially inductive and not only constitutive as previously proposed and, therefore, colony morphology might be the key trait responsible for controlling dehydration rate essential for DT inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Many factors can impact the outcome of a desiccation event including the minimum water content of dried tissues (i.e., the intensity of drying) (Gaff, 1989; Watkins et al, 2007; Marks et al, 2016), the rate of drying (Oliver et al, 1998; Farrant et al, 1999; Cruz de Carvalho et al, 2011, 2019; Stark et al, 2013; Greenwood and Stark, 2014; Greenwood et al, 2019; McLetchie and Stark, 2019), the light and temperature conditions during drying and rehydration (Hearnshaw and Proctor, 1982; Seel et al, 1992; Guo and Zhao, 2018), the duration that tissues are maintained in a dry state (Benkő, 2002), and the condition of tissues before drying (Schonbeck and Bewley, 1981; Beckett et al, 2005a, b; Brinda et al, 2016) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can impact the outcome of a desiccation event including the minimum water content of dried tissues (i.e., the intensity of drying) (Gaff, 1989; Watkins et al, 2007; Marks et al, 2016), the rate of drying (Oliver et al, 1998; Farrant et al, 1999; Cruz de Carvalho et al, 2011, 2019; Stark et al, 2013; Greenwood and Stark, 2014; Greenwood et al, 2019; McLetchie and Stark, 2019), the light and temperature conditions during drying and rehydration (Hearnshaw and Proctor, 1982; Seel et al, 1992; Guo and Zhao, 2018), the duration that tissues are maintained in a dry state (Benkő, 2002), and the condition of tissues before drying (Schonbeck and Bewley, 1981; Beckett et al, 2005a, b; Brinda et al, 2016) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the species and the conditions under which the tissues were dried and stored, resurrection plants can remain viable for months, years, or even decades in a desiccated state (Hosokawa and Kubota, 1957; Gaff, 1989; Alpert, 2000; Farrant and Kruger, 2001; Benkő, 2002; Proctor, 2003). Artificial manipulation of these variables can lead to contrasting recovery outcomes within a single species (Farrant et al, 1999; Cruz de Carvalho et al, 2011, 2019; Stark et al, 2013; Greenwood and Stark, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several bryophyte studies using a field approach concluded that photosynthesis reactions in Syntrichia and other species are capable of recovering in seconds (essentially constitutive) after the addition of liquid water (e.g., Proctor and Smirnoff, 2000; Oliver et al, 2005). This rapid rate of recovery (due to prior hardening) lent credence to the hypothesis that most clades of bryophytes were CDT (Oliver et al, 2000; Proctor et al, 2007b; Toldi et al, 2009), which has subsequently been questioned through several experiments indicating that inducible processes operating during a slow‐dry or partial‐dry event are probably widespread in bryophytes (e.g., Werner et al, 1991; Pressel and Duckett, 2010; Cruz de Carvalho et al, 2014, 2019; Greenwood and Stark, 2014; Hájek and Vicherová, 2014; Brinda et al, 2016; Bu et al, 2017; Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Sphagnum L., Hajek & beckett 2008) and even in aquatic mosses that undergo seasonal inundation (e.g. Fontinalis Hedw., Cruz de Carvalho et al 2019). The suite of mechanisms involved in DT are controlled by traits at the anatomical, physiological, and molecular level, all operating in concert during periods of drying, while desiccated, and when rehydrating (Oliver et al 2000, Proctor et al 2007).…”
Section: Desiccation Tolerancementioning
confidence: 99%